2014
DOI: 10.1103/physreva.90.022515
|View full text |Cite
|
Sign up to set email alerts
|

Interatomic-Coulombic-decay-induced recapture of photoelectrons in helium dimers

Abstract: We investigate the onset of photoionization shakeup induced interatomic Coulombic decay (ICD) in He2 at the He + * (n = 2) threshold by detecting two He + ions in coincidence. We find this threshold to be shifted towards higher energies compared to the same threshold in the monomer. The shifted onset of ion pairs created by ICD is attributed to a recapture of the threshold photoelectron after the emission of the faster ICD electron. PACS numbers:Excited ions can get rid of their excess energy via the emissio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…Furthermore, even the two measured curves exhibit some disagreement, whereas they were expected to follow the same ICD dynamics. The reason for this difference is the fact that the probability for recapture of the photoelectron [36] strongly depends on the photoelectron energy: the lower the photoelectron energy, the more likely a recapture can occur, which consequently truncates the decay-time measurement at a certain minimal time value.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, even the two measured curves exhibit some disagreement, whereas they were expected to follow the same ICD dynamics. The reason for this difference is the fact that the probability for recapture of the photoelectron [36] strongly depends on the photoelectron energy: the lower the photoelectron energy, the more likely a recapture can occur, which consequently truncates the decay-time measurement at a certain minimal time value.…”
Section: Resultsmentioning
confidence: 99%
“…The theoretical approach employed in this work accounts only for the ICD process, thus neglecting the PCI effect. While it was shown that the correlation between the photoelectron and the Auger electron may affect the spectra in the Auger decay of atoms [60], it should be noted that the two-step approach used in this work has been successfully applied to describe the experimental observations in a related experiment on He dimers [36].…”
Section: Chemical Science Accepted Manuscriptmentioning
confidence: 99%
See 2 more Smart Citations
“…It turns out, that the range of accessible decay times and in particular the minimum accessible decay time is determined by the initial energy of the photoelectron prior to PCI. This is due to the fact that electrons experiencing a strong decelaration may be recaptured into the ion [45]. As the initial photoelectron energy E p is increased, the minimum accessible decay time decreases.…”
Section: Time-resolving Synchrotron Measurements Employing Post Collimentioning
confidence: 99%